The meaning of relativity - Einstein, Albert (Princeton University, 2012)
Consists of the text of Einstein's Stafford Little Lectures, delivered in May, 1921 at Princeton University. Includes an appendix discussing advances in the theory of relativity since 1921, and an appendix on his Generalized Theory of Gravitation.